Cut sunflower as an alternative income in the southern Agreste of Pernambuco - Alves, Leonardo Zacarias; Carvalho, Josabete Salgueiro Bezerra de; Barros, Ana Marcela Ferreira; Tomiozzo, Regina; Uhlmann, Lilian Osmari; Streck, Nereu Augusto (Ornamental Horticulture, 2025)
Brazil presents optimal conditions for the cultivation of many species of ornamental plants, including cut sunflower (Helianthus annuus L.). The objective in this study was to evaluate the growth and flower production components of cut sunflower in three locations in the southern Agreste of Pernambuco, aiming to contribute to the diversification of production and income for small landholder farmers in the region. The study was carried out in the municipalities of Garanhuns, Bom Conselho and Canhotinho, State of Pernambuco, Brazil, with the cut sunflower Vincent’s Choice hybrid, considered one of the best cut flower hybrids in Brazil. The beds were 1.0 meter wide and 3.15 meters long and 10 plants per bed were evaluated in each location. Management practices from sowing to harvesting followed the recommendations of the ‘Flowers for All’ Project. The results showed a significant difference in all morphophysiological variables. It is concluded that (i) the production of cut sunflowers is adapted to the studied areas, with the standards required for the local market of the southern Agreste of Pernambuco, and that (ii) the ‘Flowers for All’ Project through the cultivation of cut sunflower contributed to the diversification of production and thus became a viable alternative for small landholder farmers in the region.